By the campfire. Pyrotechnology and Middle Stone Age hearths at Sibudu Cave - Bentsen, Silje Evjenth (My University, 2014)
The Middle Stone Age rock shelter site Sibudu contains abundant evidence of pyrotechnology (the controlled use of fire) such as combustion features, ashy layers and lenses and burned bone. I study the use, reuse and discard of fire at Sibudu and the layers Brown/Grey mix and Brown under Yellow Ash 2(i) from the post-Howiesons Poort (post-HP) industry (c. 58 000 years BP) and the layers Pinkish Grey Sand and Pinkish Grey Sand 2 from the Howiesons Poort (HP) techno-tradition (c. 65 000 years BP) are selected for detailed studies. I describe properties of selected combustion features, such as size, form, number of hearth strata, contents (bone, charcoal and stone) and pH values. The post-HP combustion features generally contain a higher proportion of charcoal and are more acidic than the HP combustion features, suggesting post-depositional differences. Twenty actualistic experiments including 39 experimental fires constitute the largest component and contribution of this thesis. The experiments were conducted in two cycles; the first cycle of experiments burned (in different fires) one each of the wood taxa Casuarina equisetifolia, Dichrostachys cinerea, Eucalyptus globulus or Acacia erioloba and the second cycle of experiments burned Dichrostachys cinerea exclusively. Variables such as wood mass, topsoil horizon and number of sequential fires were carefully controlled. The surface and subsurface temperatures of the experimental fires were recorded. The experimental hearths were excavated using similar techniques as those used at Sibudu. Surface temperatures vary greatly even under similar environmental conditions, but subsurface temperatures are more predictable. Five kilograms of wood is sufficient to produce high temperatures for several hours, and slowly adding logs to a fire ensures even temperatures. Sibudu's hearths have a basal black layer with charcoal, but experimental fires do not. Instead they produced 2 – 5 distinct strata, and long-burning fires produced more strata than short-burning ones. Experimental ash dumps lack strata. Areal extent of a hearth is dependent on the wood mass burned, but its depth is dependent on the wood taxon burned. I present spatial analysis of charcoal, bone and knapped stone from the selected Sibudu layers using Kernel density estimation. Higher densities of bone, charcoal and stone are present in the post-HP layers than in the HP. Specialist studies of wood taxa, micromorphology and organic petrology are also included. No specific firewood taxa were preferred, but herbaceous plants were burned at 65 000 years ago, suggesting short fires. This thesis provides a foundation for future research on fire-related behaviour at Sibudu and other Middle Stone Age sites. For example, higher acidity was recorded in the post-HP than in the HP combustion features; this could be caused by different diagenesis and geoarchaeological studies need to be conducted to resolve the issue.. In addition, all the primarily deposited archaeological combustion features in this study were underlain by a basal black layer rich in charcoal, but such layers did not develop in the experimental combustion features and I cannot explain this difference. Thus it is necessary to conduct more studies of the variables affecting the formation and preservation of combustion features. One aspect to study experimentally is the range of attributes controlling surface temperatures of campfires. Amongst the experiments described here, experimental fires burning five kg wood produced maximum surface temperatures in the range of 132 - 848°C, which demonstrates that surface temperatures are unpredictable. The implication is that producing particular temperatures of a fire is not straight-forward and that prehistoric fire users needed planning abilities and a thorough knowledge of pyrotechnology. Both these skills require mental abilities like those of modern people and they also require a sophisticated understanding of environmental conditions.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2014.
Keywords: Prehistoric people--South Africa--Fire use.; Archeologists--South Africa--Sibudu Cave.; Mesolithic period.